1993
DOI: 10.1007/bf00188501
|View full text |Cite
|
Sign up to set email alerts
|

The influence of instantaneous velocity gradients on turbulence properties measured with multi-sensor hot-wire probes

Abstract: The necessary assumption that the instantaneous flow field seen by hot-wire probes with two or more sensors is uniform, i.e. that all sensors are cooled by identically the same instantaneous velocity field, is often quite erroneous in highly sheared turbulent flow, such as near the wall in a turbulent boundary layer. Intense local shear layers occur, resulting in large instantaneous velocity gradients across the sensing volume of the probe. The effects of these neglected velocity gradients on the ability of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…It is assumed that each X-probe measures two velocity fluctuations at the centre of the probe. For each X-probe, the binormal velocity effect is assumed to be negligible compared with the other two components (e.g., [24,39]). Park and Wallace [24] also found that the effect of the velocity gradient across each X-probe on the rms values of velocity components is within 3% even when the mean velocity gradient is large, e.g., at y+ = 30, in a turbulent boundary layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that each X-probe measures two velocity fluctuations at the centre of the probe. For each X-probe, the binormal velocity effect is assumed to be negligible compared with the other two components (e.g., [24,39]). Park and Wallace [24] also found that the effect of the velocity gradient across each X-probe on the rms values of velocity components is within 3% even when the mean velocity gradient is large, e.g., at y+ = 30, in a turbulent boundary layer.…”
Section: Methodsmentioning
confidence: 99%
“…For each X-probe, the binormal velocity effect is assumed to be negligible compared with the other two components (e.g., [24,39]). Park and Wallace [24] also found that the effect of the velocity gradient across each X-probe on the rms values of velocity components is within 3% even when the mean velocity gradient is large, e.g., at y+ = 30, in a turbulent boundary layer. In the present flow, the mean velocity gradient is smaller and this effect should be negligible, Since each X-probe is considered independently, the calibration procedure is the same as that for a standard X-probe.…”
Section: Methodsmentioning
confidence: 99%
“…In a turbulent flow, the flow detected by a multiple-sensor probe is not uniform across the sensing volume. The effects of the velocity gradients on multiple-sensor probe performances have been demonstrated by Vukoslav~evi6 and Wallace (1981) and Park and Wallace (1992). Vukoslav6evi6 et al (1991) used a nine-sensor probe to measure the spanwise and cross-stream velocity gradients in addition to the three components of the instantaneous velocity vector in a turbulent boundary-layer.…”
Section: Nonuniform Velocity In the Sensing Volumethe Twelve-sensor Pmentioning
confidence: 99%
“…While measured velocity components can be significantly in error when the velocity gradients are large, 16,21,22 the mean velocity gradient is not significant in the present flow. Using a range of hot-wire yaw factors corresponding to these experimental conditions, errors in neglecting the fluctuating instantaneous velocity gradients are estimated to be about 3% and 4% for u rms and v rms (or w rms ), respectively, where u, v, and w are the velocity fluctuations in the x, y, and z directions, respectively.…”
Section: Methodsmentioning
confidence: 78%